On addiction the rolled steel to strain aging at drawing process. - Парусов, Э.В.; Сычков, А.Б.; Губенко, С.И.; Парусов, О.В.; Амбражей, М.Ю. (Problems of Tribology, 2016)
The influence of the chemical composition of the steel in the tendency to strain aging the rolled steel at various temperatures was researched. It was shown that boron steels have a more stable values of mechanical properties at temperatures of a real process (drawing) 150…300 С, which allows a high degree of accuracy( 30 МPа) to predict the strength class of cold-wire, as well as improve the technological plasticity rolled steel at drawing . The steel without boron as compared with a boron rental is characterized by lower values of tensile strength, elongation localized (relative reduction) and strain hardening exponent n it was found. It was shown that an increase in pearlite interlamellar distance (S0) reduces the degree of strain hardening (n) and hence the ability of the metal to the uniform formability. This shows that S0 has a significant impact on the index of the n, acting on the dislocation of the metal substructure, emerging in the deformation process. Keywords: rolled steel, strain aging, chemical composition, mechanical properties, drawing.